MODERN FRENCH NATIONAL RESEARCH CENTERS FOR THE STUDY OF CENTRAL ASIA: THE CENTER FOR RESEARCH ON THE IRANIAN WORLD - Yorkinoy Nasirdinova (Galaxy International Interdisciplinary Research Journal, 2022)
This article highlights the activities of the French national research centers operating in France to study the Timurid East. The history of the formation of the Center for Iranian Peace Studies is briefly given. It is supplemented by information about the scientific career of Ms. Maria Szuppe - director of the СERMI of CNRS